Building Green Brand Advocacy: Examining the Effect of Green Brand Image and Green Perceived Value on Green Brand Evangelism through Green Trust Mediation - Marsha Adilla Rahmani; Mahir Pradana; Arry Widodo (Transpublika Publisher, 2025)
Environmental awareness has influenced consumer behavior, particularly in choosing eco-friendly products. The Body Shop, known for its commitment to sustainability, stands out for its Green Brand Image and Green Perceived Value. This study aims to examine the impact of green brand image and green perceived value on green brand evangelism, with green trust as a mediating variable. The SOR Theory is applied in this research, explaining how stimulus variables affect the organism, resulting in a response (green brand evangelism). The study targets The Body Shop consumers in Greater Bandung and uses a quantitative method supported by descriptive analysis. Data was collected through an online questionnaire, with 388 valid responses from 390 submissions. Analysis was conducted using PLS-SEM with Smart-PLS software. Findings show a positive and significant relationship between Green Brand Image and Green Perceived Value, which influences Green Trust. Both variables also positively and significantly affect Green Brand Evangelism, directly and indirectly, through Green Trust. Green Trust plays a crucial role in mediating and strengthening the relationship between Green Brand Image and Green Perceived Value on Green Brand Evangelism. This research offers theoretical and practical insights for companies in developing green marketing strategies and maintaining consumer trust by building a strong image and delivering consistent value. The study is limited to The Body Shop consumers in Greater Bandung. Thus, future research is encouraged to expand the geographical scope for broader generalization.